The Influence of Safety, Health, and Discipline on Work Productivity in PT. Sandabi Indah Lestari (SIL) Seluma - Tito Sarwono; Ahmad Soleh; Ida Ayu Made Er. M. Gayatri (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the influence of safety, health, and discipline on work productivity in PT. Sandabi Indah Lestari (SIL) Seluma, either partially or simultaneously. Methods of data collection using a questionnaire given to 150 permanent daily employees in PT. Sandabi Indah Lestari (SIL) Seluma. The data analysis used is quantitative analysis, with multiple linear regression methods, determination test, t test and F test. The results of SPSS 16.0 obtained multiple linear regression equations, namely Y = 5.059 + 1.087X1 + (-0.312) X2 + 0.0897 X3. The regression equation shows that there is a positive influence between work safety and work discipline, as well as a negative influence of health variables on work productivity at PT. Sandabi Indah Lestari (SIL) Seluma, and the work safety variable has the strongest influence on work productivity because it has the largest regression coefficient value, namely 1.087. From the results of the determination test, it is known that 94.5% of work productivity at PT. Sandabi Indah Lestari (SIL) Seluma, is influenced by work safety, occupational health, and work discipline. The t test results show that safety, health, and work discipline partially have a significant influence on the daily work productivity of regular employees, because the probability value is sig. <0.05. While the results of F test (Anova) show that safety, health, and work discipline simultaneously have a significant influence on work productivity of permanent daily employees at PT. Sandabi Indah Lestari (SIL) Seluma, where the value of Fcount > Ftable (854.352 > 2.67).